2008
DOI: 10.1590/s1516-89132008000700024
|View full text |Cite
|
Sign up to set email alerts
|

Uncaria tomentosa extract: evaluation of effects on the in vitro and in vivo labeling of blood constituents with technetium-99m

Abstract: The influence (in vivo and in vitro)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
1
0
Order By: Relevance
“…These results confirm our hypothesis that secondary metabolites of the flavonoid type give the antioxidant characteristic to these extracts. Previous research had demonstrated that the genus Nectandra is rich in metabolites, such as polyphenols, flavonoids, and alkaloids, that confer analgesic, anti-inflammatory, and antioxidant activities (Le Quesne et al, 1980;Filho et al, 2004;Oliveira De Melo et al, 2006;Moreno et al, 2011;Ponci et al, 2015;Espitia Corredor et al, 2016). Additionally, some investigations suggested that some polyphenols have biological activities, such as transcription factors agonists (LXR agonist), BACE inhibition, and anti Aβ aggregation activity, that give the extracts from Nectandra potential action against AD (Park et al, 2004;Ondeyka et al, 2005;Wang and Du, 2009;Paula et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…These results confirm our hypothesis that secondary metabolites of the flavonoid type give the antioxidant characteristic to these extracts. Previous research had demonstrated that the genus Nectandra is rich in metabolites, such as polyphenols, flavonoids, and alkaloids, that confer analgesic, anti-inflammatory, and antioxidant activities (Le Quesne et al, 1980;Filho et al, 2004;Oliveira De Melo et al, 2006;Moreno et al, 2011;Ponci et al, 2015;Espitia Corredor et al, 2016). Additionally, some investigations suggested that some polyphenols have biological activities, such as transcription factors agonists (LXR agonist), BACE inhibition, and anti Aβ aggregation activity, that give the extracts from Nectandra potential action against AD (Park et al, 2004;Ondeyka et al, 2005;Wang and Du, 2009;Paula et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Interfere na ligação e leitura dos radiocomplexos e leitura dos elementos sanguíneos Estudo in vitro [74] Marcador Na99mTcO4…”
Section: Anticoagulantesunclassified
“…Isso pode diminuir a visualização do órgão, o que pode exigir um procedimento de repetição e aumentar o potencial para erros de diagnóstico [75][76][77][78] . Esse fitoterápico também pode interferir com métodos de estimação de células sanguíneas que utilizam Tc -99m, pois, pode quelar aos íons estanosos e ou pertecnato [74] .…”
Section: Salgueiro (Salix Alba L)unclassified
“…Moreover, authors have pointed out that in nuclear medicine, it is essential the understanding and quantification of this phenomenon in order to anticipate the behavior in vivo of radiotracers (Velasques de Oliveira et al, 2010b). In addition, authors have reported that several synthetic (Nigri et al, 2002) and natural medications (Moreno et al, 2007;Moreno et al, 2008a;Moreno et al, 2008b;Moreno et al, 2008c;Souza et al, 2011) are capable of interfering with the biodistribution and/or on the radiolabeling of blood constituents. These considerations show the importance of the studies about the effect of medications on the behavior of the radiopharmaceuticals.…”
mentioning
confidence: 99%